SEMINAR HUKUM “SOSIALISASI PENINGKATAN PEMAHAMAN DAN KESADARAN TERKAIT JUDI ONLINE DAN PINJAMAN ONLINE DI WILAYAH KECAMATAN WALANTAKA” - Asnawi; Ningsih, Ratu Septia; Alia, Salsabila Rahma; Ramadhan, Alfa; Rizkillah, Muhammad Fathin; Wulansari, Rina; Kusumasari, Rosita; Laudza, Kamelia Anis (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Bina Bangsa University (UNIBA) Group 1 Student Work Lecture (KKM) activities in Lebak Wangi Village, Walantaka District, were carried out with the aim of increasing public understanding and awareness of the dangers of online gambling and online loans. This legal seminar is designed as an educational effort to provide knowledge to the community regarding the legal aspects related to these two issues, as well as the negative impacts that can arise if involved in these illegal activities. The methods used in this seminar include the delivery of material by expert speakers in the field of law, interactive discussions, and question and answer sessions. The results of this activity are expected to increase public legal awareness, so that they are more careful in dealing with the temptation of online gambling and online loan offers that are often misleading and harmful. This activity is also expected to encourage the public to report illegal activities to the authorities if they encounter them.